Analysis of household attitudes toward the purchase of livestock products and fish in Cameroon - Tambi, N.E. (Elsevier, 2001)
The need for additional information on household demand for meat and fish in Cameroon is addressed. Probit analysis involving the Heckman selectivity correction procedure is used to estimate the effects of individual and household characteristics on demand for beef, chicken, pork and fish. Results indicate that fish is a relative necessity in Cameroon and is often substituted for beef and chicken by households whose profiles include being of low income levels, having large household sizes, are of middle age and are less educated. Whereas chicken and pork substitute each other, they are each complementary to beef. The profiles of households likely to purchase beef include being married, middle age, educated and of the Muslim faith. Profiles for households most likely to increase their purchases of chicken include being of high income levels and are public sector employed. Some policy implications are provided.